Sklaverei und der Loskauf von Sklaven und Kriegsgefangenen im frühen Islam: Zwischen Theorie und Praxis - Nassery, Idris (Gefangenloskauf im Mittelmeerraum - Ein interreligiöser Vergleich)

Das Schura-Konzept - zwischen Realität und Mythos - Nassery, Idris (Macht, Religion, Politik- Wie viel Religion verträgt der Staat?)

Max Weber, die Scharia und Aspekte islamischer Wirtschaftsethik: Eine kritische Würdigung der Beobachtungen Max Webers - Nassery, Idris (Journal für Religionsphilosophie)

Blanke Machtinteressen - Wie der „Islamische Staat“ entstehen konnte - Nassery, Idris (Frankfurter Rundschau)

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)

Testing of pipe sections - Andreiev, Anatolii; Golovko, Oleksandr; Frolov, Iaroslav; Nürnberger, Florian; Wolf, Lars Oliver; Schaper, Mirko; Grydin, Olexandr (Materials Testing)
Abstract A device and the basic technology has been developed for tensile testing pipe sections samples (tensile testing PSS) for quantitative estimating ultimate tensile and yield stresses in ring samples (PSS samples) cut from pipes. This tensile testing device provides the opportunity for compensating frictional forces during the tensile test, and using exchangeable bearings, the device can be adapted to a wide assortment of pipes. Research has been carried out regarding the shape and size of a stress concentrator introduced into the sample. Relationships have been derived between the shape of the tensile loading curves and the characteristic forces for different types of stress concentrators. It is proposed to use PSS with stress concentrators to prevent plastic deformation in one of the supporting sections (this also allows to correlate the applied forces to one section). The concentrator should be introduced into the tube wall of the sample as a drilled hole. This method is comparatively simple with respect to established testing methods.

Fachdidaktisches Wissen - Validierungsstudien - Gramzow, Yvonne; Riese, Josef; Reinhold, Peter (Heterogenität und Diversität - Vielfalt der Voraussetzungen im naturwissenschaftlichen Unterricht. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bremen 2014)

Physikalisches Fachwissen in verschiedenen Studiengängen und Wissensstufen - Woitkowski, David; Riese, Josef; Reinhold, Peter (Heterogenität und Diversität - Vielfalt der Voraussetzungen im naturwissenschaftlichen Unterricht. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bremen 2014)

Modellierung und Messung des Professionswissens in der Lehramtsausbildung Physik - Riese, Josef; Kulgemeyer, Christoph; Zander, Simon; Borowski, Andreas; Fischer, Hans E.; Gramzow, Yvonne; Reinhold, Peter; Schecker, Horst; Tomczyszyn, Elisabeth (Kompetenzen von Studierenden: 61. Beiheft der Zeitschrift für Pädagogik)
Im Hinblick auf die Verbesserung der Lehrerbildung besteht ein hohes Interesse daran, die Struktur und Genese der Kompetenzen von Lehramtsstudierenden zu beschreiben. Die Ziele des vorgestellten Projekts liegen in der Modellierung und Messung domänenspezifischer und generischer Kompetenzen, die Lehramtsstudierende der Physik im Hochschulstudium erwerben sollen. Das Modell umfasst differenzierte Facetten des physikalischen Fachwissens und des physikdidaktischen Wissens sowie das fachspezifische Erklärungswissen in unterrichtsnahen Vermittlungssituationen. Es enthält zudem Annahmen über Zusammenhänge dieser Bereiche des Professionswissens. Ausgehend vom Modell wurden schriftliche Testinstrumente und videografierte Lehr-Lern-Rollenspiele entwickelt und bei Physik-Lehramtsstudierenden eingesetzt. Die Ergebnisse sprechen für die Validität der genutzten Testverfahren. (DIPF/Orig.)

Mathematikbezogene Kompetenzentwicklung elementarpädagogischer Fachpersonen in Intensiv-Fortbildungen - Bruns, Julia; Eichen, L. (Beiträge zum Mathematikunterricht 2015)

Entwicklung eines videobasierten Instruments zur Erhebung von Handlungsfähigkeiten elementarpädagogischer Fachpersonen im mathematischen Bereich (VimaH) - Bruns, Julia; Eichen, L. (Entwicklung mathematischer Fähigkeiten von Kindern im Grundschulalter – Tagungsband des AK Grundschule in der GDM 2015)

Entwicklung eines videobasierten Instruments zur Erhebung mathematikdidaktischer Handlungskompetenzen elementarpädagogischer Fachpersonen - Bruns, Julia; Eichen, L. (Beiträge zum Mathematikunterricht 2015)

Adaptive Förderung zur Vorbereitung auf den Übergang vom Elementar- in den Primarbereich am Beispiel des Bereichs Mathematik - Bruns, Julia; Eichen, Lars (Frühe Bildung)
Die vorliegende quasi-experimentelle Querschnittsuntersuchung verfolgt das Ziel, adaptive Förderleistungen elementarpädagogischer Fachpersonen zu erfassen und Zusammenhänge mit anderen Komponenten elementarpädagogischer Arbeit aufzudecken. Im Zentrum steht die Frage: Welcher Zusammenhang zeigt sich zwischen der Beobachtungsintensität, den diagnostischen Fähigkeiten und der Qualität der adaptiven Förderpraxis im Elementarbereich? Fokussiert wird die adaptive Förderleistung einer Teilstichprobe mit n = 31 Fachpersonen in Bezug auf die Teilstichprobe von n = 62 Kinder. Dazu werden verschiedene Methoden auf Kinder- und Fachpersonenebene im Sinne eines mixed-methods Designs miteinander verknüpft (Mathematiktest ‚zahlenstark‘, standardisierte Beobachtung, standardisiertes Interview). Die Ergebnisse zeigen, dass keiner Fachperson eine optimale Förderung zweier Kinder gelingt. Im Hinblick auf den Übergang zwischen Elementar- und Primarbereich kann gefolgert werden, dass die Kinder unzureichend in ihren individuellen Bildungsprozessen begleitet werden.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Covalency of hydrogen bonds in liquid water can be probed by proton nuclear magnetic resonance experiments - Elgabarty, Hossam; Khaliullin, Rustam Z.; Kühne, Thomas D. (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Betonen – Ignorieren – Gegensteuern? Zum pädagogischen Umgang mit Geschlechtstypiken.
Im Kontext von Schule sind gleichzeitig offensiv geschlechterbetonende wie auch Geschlechterstereotypen wiedersprechende Maßnahmen zu finden. In diesem Buch sollen diese widersprüchlichen Tendenzen verstanden und die Konsequenzen für den pädagogischen Alltag aufgezeigt werden. Den Hintergrund des Buches bildet die Beobachtung, dass momentan gleichzeitig offensiv geschlechterbetonende wie auch Geschlechterstereotypen widersprechende und ausgleichende Maßnahmen im Kontext von Schule zu finden sind – und eine zunehmende Vielfalt von geschlechterbetonenden Marktangeboten. Im Rahmen eines vom BMBF geförderten Projekts sind Wissenschaftler/innen und Fachkräfte aus der Praxis zusammengekommen, um diese aktuellen Auffälligkeiten zu diskutieren. Im Zentrum steht das Anliegen, diese widersprüchlichen Tendenzen zu verstehen, es geht aber ebenso um die Frage, wie sie im pädagogischen Alltag beantwortet werden können und sollten.

Erkenntnis, Wissen, Intervention - Geschlechterwissenschaftliche Perspektiven
Der Band beschäftigt sich aus einer feministischen Perspektive mit Wechselwirkungen zwischen Erkenntnis, Wissen und Intervention auf wissenschaftlicher und gesellschaftlicher Ebene. Von jeher war es zentrales Anliegen feministischer Theoriediskurse, durch Veränderungen der Wissensbestände in Alltag und Wissenschaften neue und andere Erkenntnisprozesse zu ermöglichen und sie als Intervention in gesellschaftliche Machtverhältnisse und Alltagsroutinen wissenschaftlich und politisch produktiv werden zu lassen. Mit der doppelten Bewegung von Erkenntnis und Wissen als Intervention und Intervention in Erkenntnis, Wissen und Gesellschaft befassen sich alle Beiträge des vorliegenden Bandes. Sie nehmen Dynamiken und Wechselbeziehungen zwischen Erkenntnis, Wissen und Intervention auf wissenschaftlicher und gesellschaftlicher Ebene sowie mit Blick auf unterschiedliche Felder auf.

The optical properties of low infrared transmittance WO3-x nanocrystal thin films prepared by DC magnetron sputtering under different oxygen ratios - Xin, Y.; Zhou, H.; Ni, X.; Pan, Ying; Zhang, X.; Zheng, J.; Bao, S.; Jin, P. (RSC Advances)

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups? - Ortmann, Regina (Die Betriebswirtschaft)

Investitionsneutrale Besteuerung des ökonomischen Gewinns: ein Abriss jüngerer Forschungsbeiträge - Diller, Markus; Grottke, Markus; Lorenz, Johannes (Wirtschaftswissenschaftliches Studium (WiSt))

Tax Aggressiveness of Taxpayers with Heterogenous Income and Uncertainty about Taxable Income - Diller, Markus; Lorenz, Johannes (FinanzArchiv / Public Finance Analysis)

Frankreich – Bewegung, Spiel und Sport der Heranwachsenden bei unserem Nachbarn - Grimminger-Seidensticker, Elke; Brandl-Bredenbeck, H.P. (Dritter Kinder- und Jugendsportbericht. Kinder- und Jugendsport im Umbruch)

Interkulturelle (Bewegungs-)Erziehung – Vom sportpädagogischen Konzept zum überfachlichen Fragebogen - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia (Zeitschrift für sportpädagogische Forschung)

Missachtungsprozesse unter Schülerinnen und Schülern im Sportunterricht. Sportdidaktische Konsequenzen aus einem multimethodischen Forschungsprojekt - Grimminger-Seidensticker, Elke (sportpädagogik)

Über die Bedingung der Möglichkeit historisch-kritischer Methode als Traditionskritik in der islamischen Theologie - Ghaffar, Zishan (Zwischen Glaube und Wissenschaft. Theologie in Christentum und Islam)

Geschichten vom ersten bis zum 38. Stock - Kostan, Anastassija (Turmgeschichten: Raumerfahrung und -aneignung im AfE-Turm)

Aging in digital circuits and age monitoring: Object-oriented modeling and evaluation - Sadeghi-Kohan, Somayeh; Kamran, Arezoo; Forooghifar, Farnaz; Navabi, Zainalabedin (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling resulting in timing variations and consequently reliability challenges in digital circuits. Age monitoring methods can be used to predict and deal with the aging problem. Selecting appropriate locations for placement of hardware aging monitors is an important issue. In this work we propose a procedure for selection of appropriate internal nodes in combinational clouds between pipeline stages or combinational parts of a sequential circuit to place hardware monitors that can effectively provide aging information of various components of a modern digital system. In order to implement the node selection procedure, we propose an object-oriented model. Object-oriented model of a circuit along with a probabilistic and logical simulation engine that we have developed can effectively be used for implementation and also fast evaluation of the proposed node selection mechanism. The proposed object-oriented C+ + models can be integrated into a SystemC RTL model making it possible to perform mixed-level simulation, and integrated evaluation of a complete system. We have applied our proposed scheme to several processors including MIPS, ARM, ALPHA and MiniRISC and have looked at its effectiveness for these processors.

Online self adjusting progressive age monitoring of timing variations - Sadeghi-Kohan, Somayeh; Kamal, Mehdi; McNeil, John; Prinetto, Paolo; Navabi, Zain (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling that results in timing variations. Progressive age measurement of a circuit can help a better prevention mechanism for reducing more aging. This requires age monitors that collect progressive age information of the circuit. This paper focuses on monitor structures for implementation of progressive age detection. The monitors are self-adjusting that they adjust themselves to detect progressive changes in the timing of a circuit. Furthermore, the monitors are designed for low hardware overhead, and certainty in reported timing changes.

Automating RDF Dataset Transformation and Enrichment - Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (12th Extended Semantic Web Conference, Portorož, Slovenia, 31st May - 4th June 2015)
With the adoption of RDF across several domains, come growing requirements pertaining to the completeness and quality of RDF datasets. Currently, this problem is most commonly addressed by manually devising means of enriching an input dataset. The few tools that aim at supporting this endeavour usually focus on supporting the manual definition of enrichment pipelines. In this paper, we present a supervised learning approach based on a refinement operator for enriching RDF datasets. We show how we can use exemplary descriptions of enriched resources to generate accurate enrichment pipelines. We evaluate our approach against eight manually defined enrichment pipelines and show that our approach can learn accurate pipelines even when provided with a small number of training examples.
Keywords: 2015 group_aksw sys:relevantFor:geoknow sys:relevantFor:infai sys:relevantFor:bis ngonga simba dice sherif group_aksw geoknow deer lehmann MOLE

Simplified RDB2RDF Mapping - Stadler, Claus; Unbehauen, Joerg; Westphal, Patrick; Sherif, Mohamed; Lehmann, Jens (Proceedings of the 8th Workshop on Linked Data on the Web (LDOW2015), Florence, Italy)
The combination of the advantages of widely used relational databases and semantic technologies has attracted significant research over the past decade. In particular, mapping languages for the conversion of databases to RDF knowledge bases have been developed and standardized in the form of R2RML. In this article, we first review those mapping languages and then devise work towards a unified formal model for them. Based on this, we present the Sparqlification Mapping Language (SML), which provides an intuitive way to declare mappings based on SQL VIEWS and SPARQL construct queries. We show that SML has the same expressivity as R2RML by enumerating the language features and show the correspondences, and we outline how one syntax can be converted into the other. A conducted user study for this paper juxtaposing SML and R2RML provides evidence that SML is a more compact syntax which is easier to understand and read and thus lowers the barrier to offer SPARQL access to relational databases.
Keywords: 2015 group_aksw group_mole mole stadler lehmann sherif simba dice sys:relevantFor:geoknow geoknow peer-reviewed MOLE westphal

An Optimization Approach for Load Balancing in Parallel Link Discovery - Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS 2015)
Many of the available RDF datasets describe millions of resources by using billions of triples. Consequently, millions of links can potentially exist among such datasets. While parallel implementations of link discovery approaches have been developed in the past, load balancing approaches for local implementations of link discovery algorithms have been paid little attention to. In this paper, we thus present a novel load balancing technique for link discovery on parallel hardware based on particle-swarm optimization. We combine this approach with the Orchid algorithm for geo-spatial linking and evaluate it on real and artificial datasets. Our evaluation suggests that while naïve approaches can be super-linear on small data sets, our deterministic particle swarm optimization outperforms both naïve and classical load balancing approaches such as greedy load balancing on large datasets.
Keywords: 2015 sys:relevantFor:geoknow geoknow ngonga sherif simba dice group_aksw sys:relevantFor:infai sys:relevantFor:bis SIMBA limes

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; Garcia-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Hoeffner, Konrad; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)
Keywords: 2015 group_aksw sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow lehmann ngonga MOLE sherif simba dice hoeffner geoknow wauer westphal

The GeoKnow Handbook - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; Buehmann, Lorenz; Garcia-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Hoeffner, Konrad; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Pietzsch, Rene; Isele, Robert; et al.
Keywords: 2015 group_aksw sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow lehmann ngonga MOLE sherif simba dice hoeffner geoknow westphal buehmann

Short-and medium-term effects of informal care provision on female caregivers’ health - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

Jeder zehnte Mensch war illegal - Schubert, Michael (Die neuen Deutschen. Vom Dreißigjährigen Krieg bis heute: 400 Jahre Einwanderung nach Deutschland)

Soziale Ausgrenzung und rassistische Verfolgung der Osnabrücker Sinti im Nationalsozialismus - Schubert, Michael; Cooper, Duncan (Topografien des Terrors. Nationalsozialismus in Osnabrück)

Einflüsse auf die Entwicklung der Bindungsorganisation von der frühen Kindheit in das Vorschulalter - Franke, Sebastian

Threatening customers not to return – An effective strategy for online retailers? - Feider, L.; Garnefeld, I.; Böhm, Eva (44th EMAC Annual Conference, Leuven)

Stock market reactions to customer service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (2015 AMA Winter Academic Conference, San Antonio, TX)

Recognizing value creation opportunities in business markets - Böhm, Eva; Eggert, A.; Terho, H.; Ulaga, W.; Haas, A. (2015 AMA Winter Academic Conference, San Antonio, TX)

Stock market reactions to business service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (44th EMAC Annual Conference, Leuven)

Constitutive Effects of Technological Frames in Everyday Interaction - Klowait, Nils (Sociology of Power)

Blickfinten im Basketball: Eine EEG-Studie - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. Tagungsband der 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Treffen ohne getroffen u werden: Fechter nutzen visuelle und akusti-sche Information zum Erkennen gegnerischer Angriffe - Allerdissen, M; Bläsing, Bettina; Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Der Einfluss strategischer Prozesse auf die Verarbeitung der Blickrichtung im Basketball: Eine EKP-Studie - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Abstracts of the 57th Conference of Experimental Psychologists (TeaP))

Schnell handeln ohne zu wissen warum? Die unbewusste Verarbeitung von Angriffstechniken im Kampfsport - Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. Tagungsband der 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie)

Subliminal primes elicit independent motor responses - Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Abstracts of the 57th Conference of Experimental Psychologists (TeaP))

Visuomotor priming of power and precision grips - Güldenpenning, Iris; Seegelke, Christian; Schack, Thomas (57th Concference of Experimental Psychologists (TeaP))

Neurokognition der Blicktäuschung: Eine Studie im Basketball - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Moving Minds - Crossing Boundaries in Sport Science. Abstractband zum 22. dvs-Hochschultag)

Prokrastination: Problem oder Strategie? - Klingsieck, Katrin B. (Eile mit Weile. Aspekte der Be- und Entschleunigung in Wissenschaft und Kunst)

Procrastination - Klingsieck, Katrin B.; Steel, Piers (International Encyclopedia of Social & Behavioral Science)

CFD-Untersuchung der Fluiddynamik und des Wärmeübergangs bei einphasiger Strömung im welligen Spalt zwischen Thermoblechen - Piper, Mark; Tran, Julian M.; Kenig, Eugeny Y. (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Masked priming of complex movements: perceptual and motor processes in unconscious action perception - Güldenpenning, Iris; Braun, Jelena F; Machlitt, Daniel; Schack, Thomas (Psychological Research)

Neurophysiologische Korrelate der Verarbeitung der Blickrichtung im Basketball bei der Passbeurteilung - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (The Athlete’s Brain: Neuronale Aspekte motorischer Kontrolle im Sport. 14. Jahrestagung der dvs-Sektion Sportmotorik)

Minimum participation rules in international environmental agreements: empirical evidence from a survey among delegates in international climate negotiations - Kesternich, Martin (Applied Economics)
Keywords: Economics and Econometrics

Extreme weather experiences and climate change beliefs in China: An econometric analysis - Dai, Jing; Kesternich, Martin; Löschel, Andreas; Ziegler, Andreas (Ecological Economics)
Keywords: Economics and Econometrics; General Environmental Science

Entwurf und Anwendung einer erweiterten Zustandsüberwachung zur Verlässlichkeitssteigerung selbstoptimierender Systeme - Sondermann-Woelke, Christoph
Das Wirkparadigma der Selbstoptimierung ermöglicht mechatronischen Systemen sich autonom und flexibel an veränderte Betriebssituationen anpassen zu können. Um selbstoptimierende Systeme verlässlich zu gestalten und darüber hinaus Selbstoptimierung zur Verlässlichkeitssteigerung des Systems zu nutzen, werden in dieser Arbeit der Entwurf und die Anwendung einer erweiterten Zustandsüberwachung dargestellt. Darin wird eine klassische Zustandsüberwachung mit dem Wirkparadigma der Selbstoptimierung verbunden. Für den Entwurf der erweiterten Zustandsüberwachung wird aufgezeigt, welche Schritte erforderlich sind, damit das Wirkparadigma der Selbstoptimierung genutzt und gleichzeitig das selbstoptimierende System abgesichert werden kann. Die Basis für den Entwurf der erweiterten Zustandsüberwachung stellt die Spezifikation der Prinziplösung selbstoptimierender Systeme dar. So können das System und die erweiterte Zustandsüberwachung in den frühen Phasen des Entwicklungsprozesses konsistent entworfen werden. Hinsichtlich der Anwendung werden drei Aspekte betrachtet. Erstens werden die Entwurfsschritte anhand des Anwendungsbeispiels umgesetzt und bewertet. Zweitens werden die unterschiedlichen Betriebsstrategien auf einem realen Demonstrator implementiert und erprobt, um vor allem das Konzept des Umschaltens auf verlässlichkeitsorientierte Ziele im Fehlerfall zu bewerten. Drittens werden Simulationen durchgeführt, die über die Möglichkeiten des realen Demonstrators hinausgehen. Die exemplarische Anwendung zeigt, dass die erweiterte Zustandsüberwachung eine Steigerung der Verlässlichkeit im Betrieb mittels Selbstoptimierung ermöglicht.
Keywords: Verl{\

,,…, als habe dort niemals eine Insel gestanden.“ Wolfgang Hildesheimers und Hans Werner Henzes Das Ende einer Welt als Erzählung und Rundfunkoper - Eickmeyer, Jost; Tumat, Antje (Literatur für Leser)
An den Schluss seiner ersten unter dem programmatisch-spöttischen Titel Lieblose Legenden veröffentlichten Prosa-Sammlung setzt Wolfgang Hildesheimer effektvoll Das Ende einer Welt. Dem eschatologischen Beiklang der Rede vom Ende wird schon im Titel lakonisch Paroli geboten: Es handelt sich nur um das Ende ,,einer“ Welt, jedoch einer, die in aller hyperbolischen Absurdität mit europäischer Kunst und Kultur assoziiert werden kann, deren gewaltsamer Untergang in Diktatur und Krieg den Lesern sowohl 1952 als auch nach der letzten revidierten Publikation 1962 noch deutlich vor Augen gestanden haben dürfte. Das ,,Echte und Bleibende“, das die Marchesa di Montetristo (eine schon namentlich gekennzeichnete melancholische Version von Alexandre Dumas’ rachedurstigem Grafen) auf ihrer künstlichen Insel südöstlich von Murano pflegt, lässt sich als Sammelsurium alteuropäischer Kulturbeflissenheit lesen: an Personen ein Abraham-a-Santa-Clara-Forscher und ein Neo-Mystiker gleichen Namens, eine polnische Tänzerin, die als ,,Doppelbegabung“ (EW, 9) zugleich den Jugendstil erneuert, eine italienische Astrologin, die Kulturgeschichte betreibt, ein womöglich deutsch-italienischer monarchistischer Politiker, ein Schweizerischer Musikforscher (und -fälscher), ein französischer Flötenvirtuose und Nachfahre Jean-Pierre Bérangers, eine vermutlich irische Anhängerin keltischer Folklore. Der Palazzo der Marchesa gleicht äußerlich jenem venezianischen Gebäude, in dem Richard Wagner starb, in seinem Inneren sind gar ,,alle Stilepochen von der Gotik an vertreten“ (EW, 9), ein Cembalo gehörte einst Jean-Philippe Rameau, auch die konzertierende Flöte scheint von historischem Wert; Kleidung, Musik und die Säle, in denen sie aufgeführt wird, sind fein aufeinander abgestimmt.

"Hol dir deinen beneFIT" : Einführung eines Gesundheitspasses zur Förderung der Studierendengesundheit an der Universität Paderborn - Köster, Carolin; Schaper, Niclas; Fergland, Dennis; Bischof, Sandra; Kussin, Ulrich; Kämpfe, Astrid (Bewegungsorientierte Gesundheitsförderung an Hochschulen)

Körperlich-sportliche Aktivität und subjektiver Gesundheitszustand sowie studiumsspezifisches Stressempfinden bei Studierenden - Kämpfe, Astrid; Köster, Carolin; Brandl-Bredenbeck, Hans-Pater (Bewegungsorientierte Gesundheitsförderung an Hochschulen)

Exploring Tradeoffs between Specialized Kernels and a Reusable Overlay in a Stereo-Matching Case Study - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (International Journal of Reconfigurable Computing (IJRC))
FPGAs are known to permit huge gains in performance and efficiency for suitable applications but still require reduced design efforts and shorter development cycles for wider adoption. In this work, we compare the resulting performance of two design concepts that in different ways promise such increased productivity. As common starting point, we employ a kernel-centric design approach, where computational hotspots in an application are identified and individually accelerated on FPGA. By means of a complex stereo matching application, we evaluate two fundamentally different design philosophies and approaches for implementing the required kernels on FPGAs. In the first implementation approach, we designed individually specialized data flow kernels in a spatial programming language for a Maxeler FPGA platform; in the alternative design approach, we target a vector coprocessor with large vector lengths, which is implemented as a form of programmable overlay on the application FPGAs of a Convey HC-1. We assess both approaches in terms of overall system performance, raw kernel performance, and performance relative to invested resources. After compensating for the effects of the underlying hardware platforms, the specialized dataflow kernels on the Maxeler platform are around 3x faster than kernels executing on the Convey vector coprocessor. In our concrete scenario, due to trade-offs between reconfiguration overheads and exposed parallelism, the advantage of specialized dataflow kernels is reduced to around 2.5x.

Easy-to-Use On-The-Fly Binary Program Acceleration on Many-Cores - Damschen, Marvin; Plessl, Christian (Proceedings of the 5th International Workshop on Adaptive Self-tuning Computing Systems (ADAPT))
This paper introduces Binary Acceleration At Runtime(BAAR), an easy-to-use on-the-fly binary acceleration mechanismwhich aims to tackle the problem of enabling existentsoftware to automatically utilize accelerators at runtime. BAARis based on the LLVM Compiler Infrastructure and has aclient-server architecture. The client runs the program to beaccelerated in an environment which allows program analysisand profiling. Program parts which are identified as suitable forthe available accelerator are exported and sent to the server.The server optimizes these program parts for the acceleratorand provides RPC execution for the client. The client transformsits program to utilize accelerated execution on the server foroffloaded program parts. We evaluate our work with a proofof-concept implementation of BAAR that uses an Intel XeonPhi 5110P as the acceleration target and performs automaticoffloading, parallelization and vectorization of suitable programparts. The practicality of BAAR for real-world examples is shownbased on a study of stencil codes. Our results show a speedup ofup to 4 without any developer-provided hints and 5.77 withhints over the same code compiled with the Intel Compiler atoptimization level O2 and running on an Intel Xeon E5-2670machine. Based on our insights gained during implementationand evaluation we outline future directions of research, e.g.,offloading more fine-granular program parts than functions, amore sophisticated communication mechanism or introducing onstack-replacement.

Improving Packet Processing Performance in the ATLAS FELIX Project – Analysis and Optimization of a Memory-Bounded Algorithm - Schumacher, Jörn; T. Anderson, J.; Borga, A.; Boterenbrood, H.; Chen, H.; Chen, K.; Drake, G.; Francis, D.; Gorini, B.; Lanni, F.; Lehmann-Miotto, Giovanna; Levinson, L.; et al. (Proc. Int. Conf. on Distributed Event-Based Systems (DEBS))

Aktuelles Schlagwort: Approximate Computing - Plessl, Christian; Platzner, Marco; Schreier, Peter J. (Informatik Spektrum)
Keywords: approximate computing; survey

Transparent offloading of computational hotspots from binary code to Xeon Phi - Damschen, Marvin; Riebler, Heinrich; Vaz, Gavin Francis; Plessl, Christian (Proceedings of the 2015 Conference on Design, Automation and Test in Europe (DATE))
In this paper, we study how binary applications can be transparently accelerated with novel heterogeneous computing resources without requiring any manual porting or developer-provided hints. Our work is based on Binary Acceleration At Runtime (BAAR), our previously introduced binary acceleration mechanism that uses the LLVM Compiler Infrastructure. BAAR is designed as a client-server architecture. The client runs the program to be accelerated in an environment, which allows program analysis and profiling and identifies and extracts suitable program parts to be offloaded. The server compiles and optimizes these offloaded program parts for the accelerator and offers access to these functions to the client with a remote procedure call (RPC) interface. Our previous work proved the feasibility of our approach, but also showed that communication time and overheads limit the granularity of functions that can be meaningfully offloaded. In this work, we motivate the importance of a lightweight, high-performance communication between server and client and present a communication mechanism based on the Message Passing Interface (MPI). We evaluate our approach by using an Intel Xeon Phi 5110P as the acceleration target and show that the communication overhead can be reduced from 40% to 10%, thus enabling even small hotspots to benefit from offloading to an accelerator.

FELIX: a High-Throughput Network Approach for Interfacing to Front End Electronics for ATLAS Upgrades - Anderson, J; Borga, A; Boterenbrood, H; Chen, H; Chen, K; Drake, G; Francis, D; Gorini, B; Lanni, F; Lehmann Miotto, G; Levinson, L; Narevicius, J; et al. (Journal of Physics: Conference Series)
The ATLAS experiment at CERN is planning full deployment of a new unified optical link technology for connecting detector front end electronics on the timescale of the LHC Run 4 (2025). It is estimated that roughly 8000 GBT (GigaBit Transceiver) links, with transfer rates up to 10.24 Gbps, will replace existing links used for readout, detector control and distribution of timing and trigger information. A new class of devices will be needed to interface many GBT links to the rest of the trigger, data-acquisition and detector control systems. In this paper FELIX (Front End LInk eXchange) is presented, a PC-based device to route data from and to multiple GBT links via a high-performance general purpose network capable of a total throughput up to O(20 Tbps). FELIX implies architectural changes to the ATLAS data acquisition system, such as the use of industry standard COTS components early in the DAQ chain. Additionally the design and implementation of a FELIX demonstration platform is presented and hardware and software aspects will be discussed.

Einleitung: Organisationen und Konventionen - Knoll, Lisa (Organisationen und Konventionen)

Organisationen und Konventionen. Die Soziologie der Konventionen in der Organisationsforschung

The Hidden Regulation of Carbon Markets - Knoll, Lisa (Historical Social Research)

MiLeNa – ein überregionales Programm zur MINT-Lehrernachwuchsförderung - Salinga, Christian; Heinke, Heidrun; Jonas-Ahrend, Gabriela; Theyßen, Heike; Bahr, Ursula; Erb, Roger

Einrichten - Bartz, Christina (Historisches Wörterbuch des Mediengebrauchs)

Bewertungsfernsehen - Bartz, Christina (Pop. Kultur & Kritik H. 7)

Kriegsausbruch, Kriegs Ausbruch, KriegsAusbruch: About the possible connection between linguistic variety and age, based on personal journals from 1892-1944 - Schuster, Britt-Marie (The lifespan perspective)
Keywords: Kommunikationsgeschichte

Wie geht’s (Dir)? Zur diachronen Entwicklung pragmatischer Phraseme im kontrastiven Vergleich - Schuster, Britt-Marie (Sektion A1. Beziehungsgestaltung durch Sprache. Akten des XIII. Internationalen Germanistenkongresses Shanghai 2015. Germanistik zwischen Tradition und Innovation (Publikationen der Internationalen Vereinigung für Germanistik (IVG)))
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Einfachheit, Wiederholung und Kontrast: Zur Konstanz sprachlicher Verfahren in der persuasiven Kommunikation - Schuster, Britt-Marie (Wirksame Rede im Frühneuhochdeutschen: Syntaktische und textstilistische Aspekte)
Keywords: Kommunikationsgeschichte

Wirksame Rede im Frühneuhochdeutschen: Syntaktische und textstilistische Aspekte - Schuster, Britt-Marie; Dogaru, Dana
Keywords: Kommunikationsgeschichte

Aligning training models with smartphone properties in WiFi fingerprinting based indoor localization - Hoang, Manh Kha; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (40th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2015))

„Unwälzbar ist der Stein ,es war': ewig müssen auch alle Strafen sein!" - Corall, Niklas (Nietzscheforschung)
Keywords: General Engineering

Heilige Wesen - Lebewesen - Corall, Niklas (Nietzscheforschung)
Keywords: General Engineering

Organizations, Climate Change, and Transparency - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank (Organization & Environment)
The debate surrounding climate change often centers on companies’ contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

The Philosophy of the Marburg Neo-Kantians - Luft, Sebastian (New Approaches to Neo-Kantianism)

Next Generation, Secure Cloud-based Pan-European Information System for Enhanced Disaster Awareness for Crisis Response and Management - Kuhnert, Maike; Wietfeld, Christian; Paterour, Olivier; Georgiev, Alexander; Petersen, Katrina; Büscher, Monika; Pottebaum, Jens (12th Proceedings of the International Conference on Information Systems for Crisis Response and Management, Krystiansand, Norway, May 24-27, 2015)
Keywords: Ver{\

Designing with Users: Co-Design for Innovation in Emergency Technologies for Crisis Response and Management - Petersen, Katrina; Büscher, Monika; Kuhnert, Maike; Schneider, Steffen; Pottebaum, Jens (12th Proceedings of the International Conference on Information Systems for Crisis Response and Management, Krystiansand, Norway, May 24-27, 2015)
Keywords: Ver{\

Additive Manufacturing for Future Repair and Maintenance for the Aerospace Industry - Pottebaum, Jens; Lindemann, Christian-Friedrich; Deppe, Gereon; Koch, Rainer (Aviation in Europe - Innovating for Growth, Proceedings of the Sventh European Aeronautics Days)

Geschichte schreibend lernen - Hartung, Olaf (Schreiben als Lernen. Kompetenzentwicklung durch Schreiben (in allen Fächern))

Generisches Geschichtslernen. Drei Aufgabentypen im Vergleich - Hartung, Olaf (Zeitschrift für Geschichtsdidaktik)

Die "sich ewig wiederholende Arbeit" des Geschichtsbewusstseins - Sprache als Medium des historischen Lernens - Hartung, Olaf (Zeitschrift für Geschichtsdidaktik)

Lehrkompetenzen in der wissenschaftlichen Weiterbildung, Konzepte, Forschungsansätze und Anwendungen

Puzzling History. The Fragments of Fabius Pictor - Moritz, Tilman (Ancient Warfare Magazine)

Cross-cutting organizational and demographic divides and the performance of research and development teams: two wrongs can make a right - Iseke, Anja; Kocks, Birgit; Schneider, Martin; Schulze-Bentrop, Conrad (R&D Management)

Ein literarischer ›Versuch‹ im Experimentierfeld Zeitschrift. Medieneffekte der Deutschen Rundschau auf Gottfried Kellers Sinngedicht - Gretz, Daniela (ZfdPh)

Raman scattering efficiency in LiTaO3 and LiNbO3 crystals - Sanna, Simone; Neufeld, Sergej; Rüsing, Michael; Berth, Gerhard; Zrenner, Artur; Schmidt, Wolf Gero (Physical Review B)
LiTaO3 and LiNbO3 crystals are investigated here in a combined experimental and theoretical study that uses Raman spectroscopy in a complete set of scattering geometries and corresponding density-functional theory calculations to provide microscopic information on their vibrational properties. The Raman scattering efficiency is computed from first principles in order to univocally assign the measured Raman peaks to the calculated eigenvectors. Measured and calculated Raman spectra are shown to be in qualitative agreement and confirm the mode assignment by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)], thus finally settling a long debate. While the two crystals show rather similar vibrational properties overall, the E-TO9 mode is markedly different in the two oxides. The deviations are explained by a different anion-cation bond type in LiTaO3 and LiNbO3 crystals.

Can service learning foster a social responsibility among students? – A didactical analysis and empirical case-study in business education at a German university - Gerholz, Karl-Heinz; Losch, Simone (Corporate Social Responsibility: Locating the Missing Link)

An Overview of Topic Discovery in Twitter Communication through Social Media Analytics - Chinnov, Andrey; Kerschke, Pascal; Meske, Christian; Stieglitz, Stefan; Trautmann, Heike (Proceedings of the 20$^th$ Americas Conference on Information Systems (AMCIS ’15))
The need for automatic methods of topic discovery in the Internet grows exponentially with the amount of available textual information. Nowadays it becomes impossible to manually read even a small part of the information in order to reveal the underlying topics. Social media provide us with a great pool of user generated content, where topic discovery may be extremely useful for businesses, politicians, researchers, and other stakeholders. However, conventional topic discovery methods, which are widely used in large text corpora, face several challenges when they are applied in social media and particularly in Twitter – the most popular microblogging platform. To the best of our knowledge no comprehensive overview of these challenges and of the methods dedicated to address these challenges does exist in IS literature until now. Therefore, this paper provides an overview of these challenges, matching methods and their expected usefulness for social media analytics.

Detecting Funnel Structures by Means of Exploratory Landscape Analysis - Kerschke, Pascal; Preuss, Mike; Wessing, Simon; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO ’15))
In single-objective optimization different optimization strategies exist depending on the structure and characteristics of the underlying problem. In particular, the presence of so-called funnels in multimodal problems offers the possibility of applying techniques exploiting the global structure of the function. The recently proposed Exploratory Landscape Analysis approach automatically identifies problem characteristics based on a moderately small initial sample of the objective function and proved to be effective for algorithm selection problems in continuous black-box optimization. In this paper, specific features for detecting funnel structures are introduced and combined with the existing ones in order to classify optimization problems regarding the funnel property. The effectiveness of the approach is shown by experiments on specifically generated test instances and validation experiments on standard benchmark problems.

Evaluation of a Multi-Objective EA on Benchmark Instances for Dynamic Routing of a Vehicle - Meisel, Stephan; Grimme, Christian; Bossek, Jakob; Wölck, Martin; Rudolph, Guenter; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO ’15))
We evaluate the performance of a multi-objective evolutionary algorithm on a class of dynamic routing problems with a single vehicle. In particular we focus on relating algorithmic performance to the most prominent characteristics of problem instances. The routing problem considers two types of customers: mandatory customers must be visited whereas optional customers do not necessarily have to be visited. Moreover, mandatory customers are known prior to the start of the tour whereas optional customers request for service at later points in time with the vehicle already being on its way. The multi-objective optimization problem then results as maximizing the number of visited customers while simultaneously minimizing total travel time. As an a-posteriori evaluation tool, the evolutionary algorithm aims at approximating the related Pareto set for specifically designed benchmarking instances differing in terms of number of customers, geographical layout, fraction of mandatory customers, and request times of optional customers. Conceptional and experimental comparisons to online heuristic procedures are provided.

Improving the State of the Art in Inexact TSP Solving Using Per-Instance Algorithm Selection - Kotthoff, Lars; Kerschke, Pascal; Hoos, Holger; Trautmann, Heike (Learning and Intelligent Optimization)
We investigate per-instance algorithm selection techniques for solving the Travelling Salesman Problem (TSP), based on the two state-of-the-art inexact TSP solvers, LKH and EAX. Our comprehensive experiments demonstrate that the solvers exhibit complementary performance across a diverse set of instances, and the potential for improving the state of the art by selecting between them is significant. Using TSP features from the literature as well as a set of novel features, we show that we can capitalise on this potential by building an efficient selector that achieves significant performance improvements in practice. Our selectors represent a significant improvement in the state-of-the-art in inexact TSP solving, and hence in the ability to find optimal solutions (without proof of optimality) for challenging TSP instances in practice.

R2 Indicator Based Multiobjective Search - Brockhoff, D; Wagner, T; Trautmann, Heike (Evolutionary Computation Journal)
In multiobjective optimization, set-based performance indicators are commonly used to assess the quality of a Pareto front approximation. Based on the scalarization obtained by these indicators, a performance comparison of multiobjective optimization algorithms becomes possible. The R2 and the Hypervolume (HV) indicator represent two recommended approaches which have shown a correlated behavior in recent empirical studies. Whereas the HV indicator has been comprehensively analyzed in the last years, almost no studies on the R2 indicator exist. In this extended version of our previous conference paper, we thus perform a comprehensive investigation of the properties of the R2 indicator in a theoretical and empirical way. The influence of the number and distribution of the weight vectors on the optimal distribution of µ solutions is analyzed. Based on a comparative analysis, specific characteristics and differences of the R2 and HV indicator are presented. Furthermore, the R2 indicator is integrated into an indicator-based steady-state evolutionary multiobjective optimization algorithm (EMOA). It is shown that the so-called R2-EMOA can accurately approximate the optimal distribution of µ solutions regarding R2.

Multi-Objective Analysis of Approaches to Dynamic Routing Of a Vehicle - Grimme, C; Meisel, S; Trautmann, Heike; Rudolph, G; Wölck, M (Proceedings of the European Conference On Information Systems)
We consider a routing problem for a single vehicle serving customer Locations in the course of time. A subset of these customers must necessarily be served, while the complement of this subset contains dynamic customers which request for service over time, and which do not necessarily need to be served. The decision maker’s conflicting goals are serving as many customers as possible as well as minimizing total travel distance. We solve this bi-objective Problem with an evolutionary multi-objective algorithm in order to provide an a-posteriori evaluation tool for enabling decision makers to assess the single objective solution strategies that they actually use in real-time. We present the modifications to be applied to the evolutionary multi-objective algorithm NSGA2 in order to solve the routing problem, we describe a number of real-time single-objective solution strategies, and we finally use the gained efficient trade-off solutions of NSGA2 to exemplarily evaluate the real-time strategies. Our results show that the evolutionary multi-objective approach is well-suited to generate benchmarks for assessing dynamic heuristic strategies. Our findings point into future directions for designing dynamic multi-objective approaches for the vehicle routing problem with time windows.

Analyzing the BBOB Results by Means of Benchmarking Concepts - Mersmann, O; Preuss, M; Trautmann, Heike; Bischl, B; Weihs, C (Evolutionary Computation Journal)
We present methods to answer two basic questions that arise when benchmarking optimization algorithms. The first one is: which algorithm is the "best" one? and the second one is: which algorithm should I use for my real-world problem? Both are connected and neither is easy to answer. We present a theoretical framework for designing and analyzing the raw data of such benchmark experiments. This represents a first step in answering the aforementioned questions. The 2009 and 2010 BBOB benchmark results are analyzed by means of this framework and we derive insight regarding the answers to the two questions. Furthermore, we discuss how to properly aggregate rankings from algorithm evaluations on individual problems into a consensus, its theoretical background and which common pitfalls should be avoided. Finally, we address the grouping of test problems into sets with similar optimizer rankings and investigate whether these are reflected by already proposed test problem characteristics, finding that this is not always the case.